PURA SAMUAN TIGA SEBAGAI TEMPAT AKTIVITAS PENDIDIKAN AGAMA HINDU - Ni Ketut Menderi (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2017)
Hindus in general held a pray at SamuanTiga Temple for request to God in order to give the grace. In addition Temple also be created as place held communication among Hindus in a variety of religious activities such as Hindu religious education. Temple is also a place of Hindu religious educationwhich aim to improve the quality of knowledge and understanding of the teachings of Hinduism.Pesamuan Tiga Temple also called SamuanTiga Temple which has a variety of educational activities, namely Hinduism as a character Pasraman, stakeholders (Pemangku) training stakeholders, worker offers (banten) training, laughter yoga education, war Sampian dance and implications forsradha knowledge and Bhakti to oth Hindus.